The Body Shop "Forever Against Animal Testingâ€ - Varsha Ganatra; Rupesh Sinha; Srishti Srishti; Rudresh Pandey; Prachi Kadam; Sabillah Alfarisi Ristiansyah; Liem Gai Sin; Chong Li Yin; Daisy Mui Hung Kee; Liow Yue Jin; Ooi Yu Wei; Liew Pei Wei (International Journal of Applied Business and International Management, 2021)
Body Shop is a well-known cruelty-free cosmetics brand company. This research paper explores how Body Shop is running the campaign 'forever against animal testing' and raising its voice for banning animal testing in cosmetics. The Body Shop has been advocating for animal rights since 1989. Qualitative analysis techniques have been used in this research paper and information is obtained through a questioner focused on convenient sampling. We have discovered in our research that most consumers do not want to purchase goods which are created by harming animals. In manufacturing cosmetics, we say companies must use alternative artificial testing like Body Shop.